Hubungan Perfeksionisme, Stres Akademik, dan Fear of Missing Out (FoMO) dengan Gejala Depresi pada Pelajar SMAN 4 Mataram - Ajeng Ayu Putriyani Widodo; Irwan Syuhada; Lalu Yogi Prasetio Imam; Sabrina Intan Zoraya (Jurnal Ilmu Kedokteran dan Kesehatan Indonesia, 2026)
Depressive symptoms are one of the most common mental health problems among adolescents and may affect academic performance, social functioning, and psychological well-being. Several psychological factors are known to contribute to depressive symptoms, including perfectionism, academic stress, and fear of missing out (FoMO). This study aimed to determine the relationship between perfectionism, academic stress, and fear of missing out (FoMO) with depressive symptoms among students of SMAN 4 Mataram. This study employed an observational analytic design with a cross-sectional approach involving 306 students selected through proportionate stratified random sampling. Data were collected using the DASS-42, CAPS, ASS, and FoMO questionnaires and analyzed using univariate and bivariate analysis with the Chi-Square test. The results showed that 158 respondents (51.6%) experienced depressive symptoms, 275 respondents (89.9%) had high levels of perfectionism, 243 respondents (79.4%) experienced academic stress, and 279 respondents (91.2%) experienced FoMO. There were significant relationships between perfectionism and depressive symptoms (p = 0.014), academic stress and depressive symptoms (p = 0.001), and FoMO and depressive symptoms (p = 0.008). This study concludes that perfectionism, academic stress, and fear of missing out (FoMO) are significantly associated with depressive symptoms among students of SMAN 4 Mataram, indicating the need for early detection, strengthened counseling services, and mental health promotion programs in the school environment.